Research Progress on Quality Changes during Rehydration Process of Shiitake Mushroom - CAO Xuehui, LI Qianyu, ZHUO Qiuchen, LIANG Zhitang, ZHU Danshi (Shipin Kexue)
Fresh shiitake mushroom is rich in various nutrients such as carbohydrates, proteins, fats, vitamins and minerals, with antioxidant, anti-tumor, antibacterial and immunoenhancing effects. Due to its short storage life and susceptibility to deterioration, fresh shiitake mushroom is usually processed into dried products, which can effectively extend the storage period. The Maillard reaction during the drying process can provide a special flavor to shiitake mushroom, and the rehydration characteristics of dried shiitake mushroom are important factors determining its quality. This paper introduces the drying and rehydration processes of shiitake mushroom and the advantages and disadvantages of different rehydration methods, and reviews the characteristics of different rehydration methods, the factors affecting the rehydration process and the influence of rehydration on the quality of shiitake mushroom as well as recent progress on the modeling of rehydration kinetics. In addition, it deeply discusses the changes of texture, flavor, color and cell structure during the rehydration process of shiitake mushroom. The aim of this review is to provide new ideas and references for research on shiitake mushroom rehydration and processing.